2008
DOI: 10.1021/pr800500r
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Analysis of Primary Human T Lymphocytes Using Sequential IMAC and Titanium Oxide Enrichment

Abstract: T lymphocytes mediate cellular and humoral defense against foreign bodies or autoantigens. An understanding of T-cell information processing furthers studies of the immunological response. We describe a large-scale phosphorylation analysis of primary T cells using a multidimensional separation strategy, involving preparative SDS-PAGE for prefractionation, in-gel digestion and sequential phosphopeptide enrichment using IMAC and TiO2. A total of 281 phosphorylation sites (197 of high confidence, Ascore > 15), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 58 publications
7
64
0
Order By: Relevance
“…We observed reproducibility in phosphopeptide identifications comparable to that obtained when analyzing technical replicates of K562 lysate, suggesting that our RP-SAX-RP platform is very robust with respect to variation across biological replicates. These results highlight the analytical capabilities of RP-SAX-RP, and are particularly encouraging in the context of two recent studies, one of which identified 281 phosphorylation sites from 2 mg of biological lysate derived from partially sorted, primary lymphocytes (110), and a second which reported a total of 6248 phosphopeptides across 46 LC-MS/MS analyses of whole mouse spleens (Ϸ2 mg total protein per analysis, or 92 mg total input) (111) in a model designed to study immune response to anthrax exposure. In both studies, the samples were composed of heterogeneous cell populations, each of which will contribute a distinct signaling response to the final ensemble of phosphopeptides measured.…”
Section: Discussionsupporting
confidence: 68%
“…We observed reproducibility in phosphopeptide identifications comparable to that obtained when analyzing technical replicates of K562 lysate, suggesting that our RP-SAX-RP platform is very robust with respect to variation across biological replicates. These results highlight the analytical capabilities of RP-SAX-RP, and are particularly encouraging in the context of two recent studies, one of which identified 281 phosphorylation sites from 2 mg of biological lysate derived from partially sorted, primary lymphocytes (110), and a second which reported a total of 6248 phosphopeptides across 46 LC-MS/MS analyses of whole mouse spleens (Ϸ2 mg total protein per analysis, or 92 mg total input) (111) in a model designed to study immune response to anthrax exposure. In both studies, the samples were composed of heterogeneous cell populations, each of which will contribute a distinct signaling response to the final ensemble of phosphopeptides measured.…”
Section: Discussionsupporting
confidence: 68%
“…Over 40 000 MS/MS spectra were acquired from two samples and the data were searched against a protein target/decoy human database. 21 The target/decoy strategy is based on the principle that incorrect matches have an equal probability of being derived from either the target or the decoy database. 22,23 In contrast, spectra with relevant sequence information will match their corresponding sequence in the target database but not in the decoy database.…”
Section: Resultsmentioning
confidence: 99%
“…Correct peptide sequence identifications were evaluated using both the Xcorr score from SEQUEST and the D value, which was calculated as described. 21 Correct identifications were those with scores within the area defining a false discovery rate of o1%.…”
Section: Methodsmentioning
confidence: 99%
“…Although Jurkat cells are a very commonly accepted model to study TCR signaling (10,11,14), we have chosen here primary cells, because Jurkat cells lack specific signaling proteins as phosphatase and tensin homolog (8,15), which could result in important differences in the phosphorylation profiles after TCR stimulation. Because of the usage of primary cells, isobaric mass tags (iTRAQ) (16,17) were employed to measure differences in the phosphorylation profile after TCR stimulation.…”
mentioning
confidence: 99%